Penerokaan faktor-faktor pengetahuan teknologi pedagogi kandungan yang mempengaruhi amalan strategi pengajaran kreatif dalam pendidikan Islam - Saili, Jahidih; Taat, Muhamad Suhaimi; Awang Japilan, Nurul Hamimi (Universiti Teknologi MARA, Kedah, 2025)
The exploration of Technological Pedagogical Content Knowledge (TPCK) factors influencing the practice of creative teaching strategies in Islamic Education is becoming increasingly important in the digital era. However, the level of TPCK and the creativity in teaching practices among Islamic Education teachers remain unclear. Therefore, this study aims to identify the level of TPCK among Islamic Education teachers, analyze the relationship between TPCK components and the practice of creative teaching strategies, and determine the TPCK factors that most influence these practices. A quantitative approach with a cross-sectional survey design was employed, involving 266 Islamic Education teachers in daily secondary schools in Sabah. The findings indicate that the teachers’ TPCK level is moderately high, with content and pedagogical knowledge scoring the highest. The practice of creative teaching strategies is at a high level. Correlation analysis revealed a significant positive relationship between all TPCK components and the practice of creative teaching strategies. Multiple regression analysis identified TPCK and pedagogical content knowledge as the strongest predictors of the practice of creative teaching strategies. In conclusion, this study highlights the importance of integrating technology, pedagogy, and content to enhance the creativity of Islamic Education teachers’ teaching practices. The implications of the study include the need for training programs that focus more on TPCK integration, as well as the development of more dynamic theoretical models in the context of Islamic Education. Penerokaan faktor-faktor Pengetahuan Teknologi Pedagogi Kandungan (PTPK) yang mempengaruhi amalan strategi pengajaran kreatif dalam Pendidikan Islam semakin penting dalam era digital. Walau bagaimanapun, tahap PTPK dan amalan kreativiti pengajaran guru Pendidikan Islam masih kurang jelas. Oleh itu, kajian ini bertujuan untuk mengenal pasti tahap PTPK guru Pendidikan Islam, menganalisis hubungan antara komponen PTPK dengan amalan strategi pengajaran kreatif, dan menentukan faktor-faktor PTPK yang paling mempengaruhi amalan tersebut. Pendekatan kuantitatif dengan reka bentuk tinjauan keratan rentas digunakan, melibatkan 266 orang guru Pendidikan Islam di sekolah menengah harian di Sabah. Dapatan kajian menunjukkan tahap PTPK guru berada pada tahap sederhana tinggi, dengan pengetahuan kandungan dan pedagogi mencatatkan skor tertinggi. Amalan strategi pengajaran kreatif pula berada pada tahap tinggi. Analisis korelasi mendedahkan hubungan positif yang signifikan antara semua komponen PTPK dengan amalan strategi pengajaran kreatif. Analisis regresi berganda mengenal pasti PTPK dan pengetahuan pedagogi kandungan sebagai peramal terkuat bagi amalan strategi pengajaran kreatif. Kesimpulannya, kajian ini mendedahkan kepentingan integrasi teknologi, pedagogi, dan kandungan dalam meningkatkan kreativiti pengajaran guru Pendidikan Islam. Implikasi kajian merangkumi keperluan untuk program latihan yang lebih fokus pada pengintegrasian PTPK, serta pengembangan model teoretikal yang lebih dinamik dalam konteks Pendidikan Islam.